FORMULASI DAN EVALUASI FISIK SEDIAAN LIP CREAM DENGAN PEWARNA ALAMI DARI EKSTRAK DAUN JATI - Yunita Dian Permata Sari; Iin Suhesti; Kiky Adhianna Sulistyawati (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2022)
Leaf jati (Tectona grandis L.f.) has the pigment anthocyanin which product a red color. Anthocyanin pigments are a group of flavonoid pigments. The purpose of this study was to formulate and physically evaluate lip cream preparations with natural dyes from leaf jati extract (Tectona grandis L.f.). Anthocyanin extraction was carried out by maceration method using 96% ethanol as solvent. Lip cream was made into three formulas with different concentrations of extract leaf jati by 5%,10%,and 15%. The lip cream in each formula was subjected to physical tests including organoleptic test, homogeneity test, pH test, adhesion test, dispersion test, and hedonic test. The results of the organoleptic test of the three formulas have different colors it is pink to red because variation of leaf jati extract used. The results of the homogeneity test showed that the three formulas are homogeneous. The results of the pH test of the three formulas are 4, indicating that all formulas had met the lip pH requirements of 3.8-4.7. The results of the adhesion test are F1=2,42±0,04;F2=3.21±0,03; and F3=4.26±0,02, these results show that only F3 meets the requirements because it is more than 4 seconds. The results of the dispersion test are F1=5.35±0,02;F2=5,21±0,04;and F3=5,10±0,03, the result is qualified because the result is 5-7 cm. The result of the preference test that was most preferred based on color, aroma, moisture, and texture was formula 2. Based on the results of the One Way Anova and Kruskal Wallis tests, there were significant differences in adhesion and dispersion